Just words : Lillian Hellman, Mary McCarthy, and the failure of public conversation in America - Ackerman, Alan L. (Alan Louis) (Yale University Press, 2011)
In an appearance on The Dick Cavett Show in 1980, the critic Mary McCarthy glibly remarked that every word author Lillian Hellman wrote was a lie, "including 'and' and 'the.'" Hellman immediately filed a libel suit, charging that McCarthy's comment was not a legitimate conversation on public issues but an attack on her reputation. This intriguing book offers a many-faceted examination of Hellman's infamous suit and explores what it tells us about tensions between privacy and self-expression, freedom and restraint in public language, and what can and cannot be said in public in America.